Influence of precipitated phases on properties during prolonged aging in TP347H steel at 700 °C. (4th May 2017) - Wang, W.; Wang, Z. W.; Li, W. S.; Tian, J.; Zhong, W. L.; Lin, J. D.
Abstract: The aging of austenitic stainless steel TP347H (18% Cr-12% Ni-1% Nb) was performed at 700 °C for 500, 800, 1500, 2500 and 3650 h. Microstructure, precipitates and mechanical properties were examined on aged materials to analyze the impact of microstructure on mechanical properties. These tests showed that the main precipitate of the TP347 specimen was Nb(C, N) while M23 C6 carbides precipitated at the aging time of 500 h, with the coarsening of M23 C6 and MX phases during prolonged aging. The fine and dispersive Nb(C, N) particle precipitation up to 1500 h aging is a benefit for hardness and creep resistance. After aging for 3650 h, σ phase precipitated. Meanwhile, coarsening of Cr23 C6 and Nb(C, N) led to creep cavity and brittle intergranular fracture. No clear change in tensile properties at room temperature during aging were observed. A distinct decline in creep properties was caused by an average diameter increase and precipitation of σ phase and bulky Cr23 C6 .